Osseointegrated Implants and Osseoperception - A Review - Kumari Deepika; Atul Bhatnagar; Rekha Gupta (Journal of Multidisciplinary Dental Research)
There are many studies suggest that a peripheral feedback pathway can be restored with osseointegrated implants even after tooth loss. This implant mediated sensory-motor control, known as osseoperception may have important clinical implications in improving masticatory function with implant supported prosthesis. To understand this psychophysical integration of implants, available literature was evaluated using various online resources such as Pubmed, Google scholar, etc. using keywords like “osseoperception”, tactile sensibility, implant mediated sensory-motor control and mechanoreceptors. The long-term integration of an implant-bone restoration depends in part on optimal load distribution on the bearing tissue. Because natural teeth and implants vary in their anchorage mechanisms so there is a fundamental difference in the perception and control of the loading. The current review of literature deals with these issues and has been summarized under following heads: • Mechanism of osseoperception • Neurophysiological and psychophysical methods of assessing phenomenon of osseoperception • Mechanoreceptors contributing to osseoperception • Different concepts of osseoperception Keywords: Osseointegration, osseoperception, active threshold, passive threshold, dental implant